Original article Rosiglitazone protects the dorsal root ganglion cells and sciatic nerve after crush in rat - Noorafshan, Ali; Shariat, Khatoon; Karbalay-Doust, Saied; Omidi, Ameneh (Folia Neuropathologica, 2011)
The aim of this study was to investigate the histological changes in the dorsal root ganglion (DRG) and the sciatic nerve in rats after sciatic nerve crush (SNC) and treatment with rosiglitazone. The rats were divided into four groups, each including seven animals, and underwent the following intervention. Group I: control animals which received carboxy methyl cellulose (0.5 w/v, p.o.). Group II: sham operated animals whose skin of the posterior thigh was opened, closed and the animals received the vehicle (carboxy methyl cellulose). Group III: SNC animals; the animals received the vehicle. Group IV: SNC with rosiglitazone (5 mg/kg body weight/day) dissolved in the vehicle. On the 28th day the fifth lumbar DRG and sciatic nerve were removed. Volume of the dorsal root ganglion, total volume and number of cells (A and B cells) of DRG, total surface area of the cells, and total number, diameter and cross-sectional area of the myelinated nerve fibres were estimated using stereological techniques. No change was observed in volume of the DRG, but all of the other parameters were decreased after nerve crush. In SNC+ rosiglitazone treated rats, the parameters decreased but to a lesser extent in comparison with the non-treated SNC group. It can be concluded that rosiglitazone has a protective effect on the DRG cells and sciatic nerve after crush in rats.